The hedonic shopping and impulse buying: understanding customer motivation in the e-commerce era - Dika Argian Syah; Anisah Istiqomah; Hanip Munib Al Haqqi; Cut Farah Selene Aurelia; Masran Tamin (Ifma Publishing, 2025)
This study examines the influence of hedonic shopping, shopping lifestyle, and shopping motivation on impulse purchases among e-commerce consumers in Indonesia. With the rapid growth of Indonesia's e-commerce market, it is important to understand the psychological factors that drive consumer behavior. This study uses a descriptive quantitative approach by distributing questionnaires to 112 respondents who are e-commerce users. Independent variables are hedonic shopping and shopping lifestyle, the dependent variable is impulse buying, and the moderating variable is shopping motivation. The results show that hedonic shopping and shopping motivation significantly and positively affect impulse purchases, while shopping lifestyle does not. Furthermore, shopping motivation cannot moderate the relationship between hedonic shopping and shopping lifestyle on impulse purchases. These findings underscore the importance of emotional experience and internal motivation in driving impulse purchases in e-commerce environments.